2018
DOI: 10.1080/23761407.2018.1431576
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of the urban adolescent hope scale

Abstract: The findings from this study indicate the UAHS has initial validity and reliability to be used as a measure of hope for urban adolescents. Future implications for research and practice are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…1; (Gabrielsen et al, 2012) Hope Belief in the future and that hopes, and goals will be met (FESA Scale) Children Future Expectation Scale 1; (Zhao et al, 2011) Children's Hope Scale 2; (Ey et al, 2005;Ciarrochi et al, 2007) The Children's dispositional hope scale 1; (Vaughn et al, 2009) The Hopefulness about Future (Hope) scale 2; (Zhao et al, 2011;Canfield et al, 2018) Urban Adolescent Hope Scale 1; (Canfield et al, 2018) Life purpose/goal Feeling that one's life is significant, comprehensible, or purposeful Adolescent Life Goal Profile Scale (ALGPS)…”
Section: Mental Wellbeing [General] Experience Of Positive Mental And...mentioning
confidence: 99%
“…1; (Gabrielsen et al, 2012) Hope Belief in the future and that hopes, and goals will be met (FESA Scale) Children Future Expectation Scale 1; (Zhao et al, 2011) Children's Hope Scale 2; (Ey et al, 2005;Ciarrochi et al, 2007) The Children's dispositional hope scale 1; (Vaughn et al, 2009) The Hopefulness about Future (Hope) scale 2; (Zhao et al, 2011;Canfield et al, 2018) Urban Adolescent Hope Scale 1; (Canfield et al, 2018) Life purpose/goal Feeling that one's life is significant, comprehensible, or purposeful Adolescent Life Goal Profile Scale (ALGPS)…”
Section: Mental Wellbeing [General] Experience Of Positive Mental And...mentioning
confidence: 99%
“…Furthermore, despite the increased focus on positive mental health, a challenge of the field is the lack of consensus on how mental wellness should be conceptualized [1]. Research has identified a range of mental wellness constructs such as self-acceptance, hope, connectedness, and life satisfaction, among others, that are associated with improved well-being and positive functioning in adults and adolescents [1,24,25]. As mentioned, these concepts have mostly emerged from research in the Western context, with a number of growing studies exploring these concepts among indigenous populations and those living in the global South [26].…”
Section: Introductionmentioning
confidence: 99%